ChemInform Abstract: Novel Chiral Bifunctional L‐Thiazoline‐amide Derivatives: Design and Application in the Direct Enantioselective Aldol Reactions. Issue 31 (5th August 2014) - Gong, Zhiyong; Wei, Chiyu; Shi, Ye; Zheng, Qingchuan; Song, Zhiguang; Liu, Zaiqun
Abstract The chiral catalyst is prepared from cysteine and proline in eight steps.